Nanoparticle Engineering for Chemical-Mechanical Planarization Fabrication of Next-Generation Nanodevices - Paik, Ungyu (Taylor & Francis, 2009)
Increasing reliance on electronic devices demands products with high performance and efficiency. Such devices can be realized through the advent of nanoparticle technology. This book explains the physicochemical properties of nanoparticles according to each step in the chemical mechanical planarization (CMP) process, including dielectric CMP, shallow trend isolation CMP, metal CMP, poly isolation CMP, and noble metal CMP. The authors provide a detailed guide to nanoparticle engineering of novel CMP slurry for next-generation nanoscale devices below the 60nm design rule. This comprehensive text also presents design techniques using polymeric additives to improve CMP performance.